2010
DOI: 10.4049/jimmunol.1001159
|View full text |Cite|
|
Sign up to set email alerts
|

Polymorphic Variants of LIGHT (TNF Superfamily-14) Alter Receptor Avidity and Bioavailability

Abstract: The TNF superfamily member homologous to lymphotoxins, exhibits inducible expression, and competes with HSV glycoprotein D for herpesvirus entry mediator (HVEM), a receptor expressed by T lymphocytes (LIGHT) [TNF superfamily (SF)-14], is a key cytokine that activates T cells and dendritic cells and is implicated as a mediator of inflammatory, metabolic, and malignant diseases. LIGHT engages the lymphotoxin-β receptor (LTβR) and HVEM (TNFRSF14), but is competitively limited in activating these receptors by solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 53 publications
(72 reference statements)
1
16
1
Order By: Relevance
“…The inflammatory cytokineTNFSF14, also known as LIGHT, is involved in cell survival and proliferation in the regulation of innate and adaptive immune response [22][23][24]. In this study, no association was found between polymorphisms in TNFSF14 and variability in weekly dose of warfarin.…”
Section: Effects Of Polymorphisms On Warfarin Dose and Time To Reach contrasting
confidence: 44%
“…The inflammatory cytokineTNFSF14, also known as LIGHT, is involved in cell survival and proliferation in the regulation of innate and adaptive immune response [22][23][24]. In this study, no association was found between polymorphisms in TNFSF14 and variability in weekly dose of warfarin.…”
Section: Effects Of Polymorphisms On Warfarin Dose and Time To Reach contrasting
confidence: 44%
“…DcR3 exists solely as a soluble molecule, obviating steric conflicts that might preclude formation of the interlocking assembly in vivo . Interestingly, a natural variant of LIGHT, E214K, which is close to the trans interaction interface (Figure S9), has been implicated in inflammatory diseases (Cheung et al, 2010). However, solution and cell-based studies failed to detect this higher order assembly and at present no direct experimental evidence exists supporting a physiological role for the interlocking dodecamer.…”
Section: Discussionmentioning
confidence: 99%
“…This network is controlled by an additional factor in primates, DcR3 ( TNFRSF6B ) that engages LIGHT, TL1A and FasL, binding with high affinity to LIGHT (Liu et al, 2014). DcR3 lacks a transmembrane domain yet localizes within tissues via a heparin binding site (Cheung et al, 2010b). A role for this regulator and its ligands in inflammation emerged with the identification of DcR3 (TNFRSF6B) deficiency in patients with early onset inflammatory bowel disease (Cardinale et al, 2013).…”
Section: Network Wiring In the Tnf Superfamilymentioning
confidence: 99%